Persepsi Penderita Penyakit Ginjal Kronik dalam Menjalani Hemodialisa - Lestarina, Ni Nyoman Wahyu; Kurniawaty, Yuni; Putri, Maria Odilia Verdy Utomo; Kevin, Johanes (Poltekkes Kemenkes Tanjung Karang, 2022)
Patients with end-stage renal failure require renal replacement therapy, one of which is hemodialysis. one of the challenges in treating CKD patients is the lack of interventions that match the beliefs, expectations, and emotional reactions associated with the disease. The purpose of this study was to determine the patient's perceptions of undergoing hemodialysis and how the patient deals with the changes that occur in him. This research is a type of qualitative research with a phenomenological method. the research was conducted in the hemodialysis room hospital in Surabaya. The research was conducted in June-July 2019. The research subjects were determined to be snowball in nature. The research subjects were 6 people, who were chronic kidney disease sufferers who performed routine hemodialysis 2-3 times a week. Data were obtained through in-depth interviews using interview guidelines. The data analysis process includes data reduction, data categorization, synthesis and ends with compiling a working hypothesis. The results of the analysis obtained several themes, namely expectations, experiences, motives, and social/family conditions. in the early stages of the disease they experience some negative disease perceptions which can ultimately affect their coping actions. The role of disease perception is to help patients develop positive disease management strategies that in turn slow the rate of disease progression and improve psychosocial outcomes.